Does industrial eco-innovative development and economic growth affect environmental sustainability? New evidence from BRICS countries - Liu, Siming; Gao, Leifu; Hu, Xuhua; Shi, Junguo; Mohsin, Muhammad; Naseem, Sobia (Frontiers in Environmental Science, 2022)
This research aims to identify the periodical impact of industrial development, renewable energy, economic growth, and gross capital formation on environmental deterioration in BRICS countries. The analytical procedure is based on the annual data from 1995 to 2020. The selected econometric methods which are employed to determine the relationship among exogenous and endogenous variables are panel unit-root tests for stationarity check, Johansen cointegration test for cointegration relationship, FMOLS and quantile regression for long-run relationship. The empirical research findings confirm a significant positive association of environmental deterioration with industrial development, GDP and GCF, while a significant negative relationship was observed between CO2 emission and renewable energy. The BRICS group of countries should be more focused on environmental friendly technological development as they are concerned with economic growth. Renewable energy resources positively impact environmental quality, so the backward resources should be replaced with renewable energy resources to attain double impacts, i.e. reduction of CO2 emission with reduction of oldfangled resources and increase environmental quality with the aggrandizement of renewable energy resources. Based on key findings and implications of sectorial and whole economic growth of BRICS countries, this research suggests some policy implications for reducing toxic CO2 emissions and enhancing the quality of the environment.